PEMBUATAN PORTABLE TRAINING KIT PNEUMATIK DASAR - , AGIL DWI HERMAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the competitive world of industry, the company is expected to produce quickly and efficiently in order to achieve the production target. One taken to increase the production is to transform manual processes into automated processes. On the other hand the application of automation can also reduce accidents caused by human error and unsafe condition. In making explanations pneumatic training kit is divided into two parts, the first is making pneumatic module consisted of pneumatic components, and the second parts is making the frame. To finish this final task, there are some methods have been done such as collecting some data related with this task, pneumatic designing machining processes, assembling, and finishing. The result of this task is the Training Kit Pneumatic simulator can be used and fully helps student to study controller comfortably. Hence, the student will understand easily.